Host-specificity and morphometrics of female Haemonchus contortus, H. placei and H. similis (Nematoda: Trichostrongylidae) in cattle and sheep from shared pastures in São Paulo State, Brazil. Issue 3 (4th March 2014) - Silva, M.R.L.; Amarante, M.R.V.; Bresciani, K.D.S.; Amarante, A.F.T.
Abstract: To better evaluate the usefulness of female Haemonchus specimens for specific identification, we undertook a detailed analysis of the morphology of a collection of worms obtained from cattle and sheep in shared pastures. Based on the results, we also more precisely evaluated the host-specificity of Haemonchus contortus, H. placei and H. similis occurring sympatrically in a farm located in the western region of São Paulo State, Brazil. A synlophe analysis was employed to identify the three species of Haemonchus . In cattle, the predominant species was H. similis (90.9%), followed by H. placei (9.1%). With the exception of one H. placei specimen, only H. contortus was found in sheep. The longest body length was found for H. placei specimens, followed by H. contortus and then H. similis. It was possible to distinguish H. similis females from H. contortus and H. placei on the basis of vulval structure. The synlophe analysis proved to be very useful for identification of H. contortus, H. placei and H. similis in epidemiological studies involving different species of ruminants in the same pastures. The finding that H. placei and H. similis were adapted to cattle and that H. contortus was adapted to sheep also confirmed the high host-specificity of the three nematodes species.